2017
DOI: 10.1007/s12035-017-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity

Abstract: Special AT-rich sequence-binding protein 2 (Satb2) is a protein binding to the matrix attachment regions of DNA and important for gene regulation. Patients with SATB2 mutation usually suffer moderate to severe mental retardation. However, the mechanisms for the defects of intellectual activities in patients with SATB2 mutation are largely unclear. Here we established the heterozygous Satb2 mutant mice and Satb2 conditional knockout mice to mimic the patients with SATB2 mutation and figured out the role of Satb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…In general, Satb2 functions as a transcriptional regulator that is important for tissue‐specific functions. In mice bone progenitors, Satb2 regulates osteogenic differentiation genes (Dobreva et al, ), while in postmitotic neurons Satb2 regulates expression of genes involved in upper layer identity, synaptic transmission, and axon guidance (Jaitner et al, ; Li et al, ; Whitton et al, ). The consequence of loss of Satb2 in bone progenitors is reduced bone size and density due to increased cell death and reduced differentiation potential (Britanova et al, ; Dobreva et al, ).…”
Section: Animal Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, Satb2 functions as a transcriptional regulator that is important for tissue‐specific functions. In mice bone progenitors, Satb2 regulates osteogenic differentiation genes (Dobreva et al, ), while in postmitotic neurons Satb2 regulates expression of genes involved in upper layer identity, synaptic transmission, and axon guidance (Jaitner et al, ; Li et al, ; Whitton et al, ). The consequence of loss of Satb2 in bone progenitors is reduced bone size and density due to increased cell death and reduced differentiation potential (Britanova et al, ; Dobreva et al, ).…”
Section: Animal Modelsmentioning
confidence: 99%
“…In murine brain development, Satb2 is required to specify upper layer cortical neurons that project axons across the corpus callosum to the contralateral hemisphere (Alcamo et al, ; Britanova et al, ). Loss of Satb2 also results in reduced branches and spine density in basal dendrites of hippocampal neurons (Li et al, ). Similar to patients with SAS, Satb2 +/‐ heterozygous mice have no reported corpus callosum defects (Alcamo et al, ; Zarate, Smith‐Hicks et al ()).…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While postnatally, Satb2 is required for proper dendritic and soma adhesion of callosal neurons in neocortex [32]. In adult, Satb2 deletion leads to impairment in long-term memory [33,34]. We also reported that mice with loss of Satb2 in cortex and hippocampus show hyperactivity, increased impulsivity, abnormal social novelty, and impaired spatial learning and memory [35].…”
Section: Introductionmentioning
confidence: 82%
“…Then posterior mPFC and VTA were sectioned out using ice-cold mouse brain mold (Cat# 68713, RWD). qRT-PCR was performed accordingly [54] by using a 7500 real-time PCR system (ABI, California, USA) and SYBR Premix Ex Taq (Cat# RR420A, Takara, Osaka, Japan). Normalized to the mRNA expression level of Gapdh or Actb, the mRNA expression of other genes was evaluated using the method of ΔΔCt.…”
Section: Quantitative Reverse Transcription Pcr (Qrt-pcr)mentioning
confidence: 99%